THE INTERACTION OF PROBLEM BASED LEARNING AND COGNITIVE STYLES ON STUDENTS’ MATHEMATICAL CREATIVE THINKING ABILITY - Agus Jaenudin (International Journal of Teaching and Learning, 2025)
This study examines the interaction between the Problem Based Learning (PBL) model and students’ cognitive styles in influencing mathematical creative thinking ability. A quasi-experimental design with a 2×2 factorial arrangement was employed, involving third-semester students of the Mathematics Education Department at Universitas Sebelas April. The experimental group (23 students) received instruction through PBL, while the control group (22 students) learned through conventional methods. Instruments included a mathematical creative thinking test and the Group Embedded Figures Test (GEFT) to identify Field Independent (FI) and Field Dependent (FD) styles. The results indicate three key findings: (1) PBL significantly outperforms conventional learning in enhancing mathematical creative thinking; (2) students with FI style show higher creative thinking scores compared to FD students; and (3) a significant interaction exists between learning model and cognitive style. Notably, PBL proves more effective for FI learners who benefit from its analytical and problem-oriented approach. These findings suggest that integrating PBL with consideration of students’ cognitive styles can better foster mathematical creative thinking. Lecturers are encouraged to design instruction that adapts to cognitive diversity, ensuring optimal learning outcomes in mathematics education.